Relación entre sobrecarga del cuidador y depresión en cuidadores de personas con discapacidad, en el Centro de Salud N°3, Loja - Prado Cueva, Khaterine Janela (2020)
It is globally known that caregivers of people with disabilities face situations of vulnerability, physical and emotional stress, leading to caregiver overload, which increases the risk of mental health problems such as depression. In our country it constitutes a great public health problem due to the high prevalence of these pathologies. The present investigation was carried out with the aim of establishing the relationship between caregiver overload and depression in caregivers of people with disabilities at Health Center No. 3, in the city of Loja in 2018. The study design is of a quantitative, analytical, cross-sectional type. The universe was made up of 109 caregivers of people with disabilities. The data from said investigation were obtained by applying two instruments: the Zarit scale and the Hamilton test, and the application of a sociodemographic record. The results obtained indicate a prevalence of caregiver overload of 77% and depression of 73.4%. The caregivers are generally women (89.9%), with an age between 35 and 64 years, with a low level of education (52.3% primary), 86.2% are dedicated to the care of people with very serious disabilities (> 75%), regarding the degree of affinity 29.4% corresponds to a relative. It was verified that there is a statistically significant relationship between the study variables (p = 0.029). Keywords: Caregivers, Disability, Zarit Test, Hamilton Test.